Treatment of an iatrogenic femoral artery pseudoaneurysm with concomitant arteriovenous fistula with percutaneous implantation of an amplatzer vascular plug1. Issue 1 (2nd May 2012) - Shetty, Ranjith; Lotun, Kapildeo
Abstract Iatrogenic pseudoaneurysms can occur following percutaneous cardiac and peripheral procedures. There are multiple modalities available for the treatment of pseudoaneurysms including ultrasound guided compression repair, ultrasound guided thrombin injection, or endovascular repair with covered stent placement. If these methods are not indicated or unsuccessful, patients typically require open surgical repair. We report a case of a woman with a post‐procedural pseudoaneurysm with concomitant arteriovenous fistula who was treated percutaneously with the implantation of an Amplatzer vascular plug. This novel technique was safe and effective and allowed our patient to avoid the morbidity and mortality associated with surgical repair. © 2012 Wiley Periodicals, Inc.